The Role and Influence of Gut Microbiota in Pathogenesis and Management of Obesity and Metabolic Syndrome - Parekh, Parth J.; Arusi, Eli; Vinik, Aaron; Johnson, David A. (Frontiers in Endocrinology, 2014)
The obesity epidemic has drastically impacted the state of health care in the United States. Aside from poor diet hygiene and genetics, there are many other factors thought to play a role in the emergence of obesity and the metabolic syndrome. There has been a paradigm shift towards further investigating the gut microbiota and its implications in the pathogenesis of a variety of disease states, including inflammatory bowel disease, Clostridium difficile, and most recently obesity and the metabolic syndrome. This article is intended to evaluate the role of gut microbiota in the pathogenesis of obesity and metabolic syndrome and its influence in future management.